Active disturbance rejection control for electric cylinders with PD-type event-triggering condition. (July 2020) - Liu, Dongchen; Wang, Junzheng; Wang, Shoukun; Shi, Dawei
Abstract: This work proposes an event-triggered active disturbance rejection control method for electric cylinder systems. Through analyzing the dynamics, disturbances, and uncertainties of an electric cylinder system with roller-screw, a proportional–derivative-type (PD-type) event-triggered sampler together with the corresponding extended state observer is introduced. The event-triggering condition is designed considering not only the size but also the trend of tracking error, based on which the nonexistence of Zeno behavior is proved. With the observation results, a closed-loop controller with guaranteed stable tracking performance is further designed. The control method is verified on an electric cylinder control system, and comparative experimental results indicate that for different reference signals, the proposed event-triggered controller can achieve satisfactory tracking performance for the electric cylinder system at a reduced sampling cost.